contestada

-3(y-5)+6y-2 simplify using distributive property and then combine like terms ANOTHER ONE PLEASE

Respuesta :

Answer:

3y+13

Step-by-step explanation:

-3(y-5)+6y-2

Distribute

-3y +15 +6y-2

Combine like terms

-3y+6y  +15-2

3y            +13

[tex]\bf \large{\purple{ \implies}} \tt \: - 3(y - 5) \: + \: 6y \: - \: 2[/tex]

[tex]\bf \large{\purple{ \implies}} \tt \: - 3y \: + \: 15 \: + \: 6y \: - 2[/tex]

[tex]\bf \large{\purple{ \implies}} \tt \: - 3y \: + \: 6y \: + \: 15 \: - \: 2[/tex]

[tex]\bf \large{\purple{ \implies}} \tt \: 3y \: + \: 13[/tex]